(8x+11)÷3=(4x+1) 两边乘38x+11=12x+312x-8x=11-34x=8x=8÷4x=23(3x+1)÷(x+12)=4 3(3x+1)=4(x+12)9x+3=4x+489x-4x=48-35x=45x=45÷5x=9(2-x)+(4x-2)=7(x-4)2-x+4x-2=7x-287x+x-4x=2-2+284x=28x=28÷4x=7
以下这些题目用移向的方法去解方程,(8x+11)÷3=(4x+1) 3(3x+1)÷(x+12)=4 (2-x)+(4x
1个回答
相关问题
-
4X÷2/3=1/8 解方程4X÷2/3=1/8
-
解方程:3x-2=x+4 8x-7.5+1.5=42 x÷3/11=4/3÷9/22 3/5x=56 x÷4/5=8/3
-
解方程:5/2+4x=3 4/1x+3/1=12/17 x÷7/3=8/1÷9/1
-
解方程 8 9 X= 1 6 × 16 51 X÷ 3 4 = 1 2 2 3 X÷ 1 4 =12.
-
解方程:12X-3.4=8 2X=3.6 X÷1.1=3.6 X+6=14.4.
-
解方程x- 3 4 x= 3 16 x÷ 3 8 = 4 9 x÷ 下 5 + 1 5 = 4 5 2 3 x=下 x÷
-
解下列方程 2(x-4)=3(x-12) x÷3+x÷2=6 0.4:x=(1+[1/7]):5.
-
解方程(X-12)÷1/4=X÷(1-3/5)
-
解方程x-[3/4]x=[3/10] x÷[3/8]=[4/9] x÷[7/5]+[1/5]=[4/5] [2/3]x=
-
几道解方程3、20+3/4x=9/10x-7/10x=11/3x-1/4x=3/45/8÷x=5/4×1/2x×5/6÷